Pengaruh Kepercayaan Dan Persepsi Risiko Terhadap Keputusan Pembelian Secara Online Pada Konsumen Shopee Di Kota Bengkulu - Rini Rahmadhana; Sri Ekowati (UNIVED Press, 2022)
This study aims to determine the effect of trust and risk perception on online purchasing decisions of shopee consumers in Bengkulu city; partially or simultaneously. There are two factors as the main focus of this study, including trust, and risk perception. The object of this research were 55 persons of shopee consumers in Bengkulu city. In this study used the method of collecting data through observation, distributing questionnaires or questionnaires. Data analysis techniques of this study used instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. The results of this study showed that the trust variable has a positive and significant effect on online purchasing decisions of Shopee consumers. Similarly, risk perception has a positive and significant impact on online purchasing decisions of Shopee consumers. Simultaneously, trust and risk perception have a positive and significant impact on online purchase decisions for shopee consumers in Bengkulu city.